Cultural Sensitivity and Systemic Support in Parenting Interventions - Cahyono, Maria Yuni Megarini; Adiawaty, Susi (Sinergi International Journal of Psychology, 2024)
Parenting and child welfare are influenced by a complex interplay of socioeconomic, psychological, and cultural factors. This study examines the impact of financial stability, parental mental health, and cultural influences on child development, emphasizing the importance of systemic interventions in mitigating challenges faced by families. A comprehensive literature review was conducted using Scopus, Google Scholar, and PubMed, focusing on empirical studies from the past five years. Key findings indicate that financial hardship exacerbates parental stress, leading to diminished child welfare outcomes, while parental mental health significantly affects parenting efficacy. Cultural contexts play a crucial role in shaping parenting practices, necessitating culturally responsive interventions. Effective solutions include peer support programs, economic assistance, and the integration of mental health services into family support frameworks. Despite the progress in research, gaps remain in understanding the long-term effects of interventions, the role of digital parenting support, and the challenges faced by diverse family structures. Policy recommendations include expanding financial aid, fostering multi-sectoral collaboration, and enhancing access to culturally adapted parenting programs. Future studies should focus on longitudinal research to assess intervention effectiveness and explore innovative solutions for improving child welfare globally. This research underscores the urgency of implementing comprehensive strategies to enhance parenting practices and promote child well-being in diverse socio-economic and cultural contexts.